Inhibiting PI3K–AKT–mTOR Signaling in Multiple Myeloma-Associated Mesenchymal Stem Cells Impedes the Proliferation of Multiple Myeloma Cells - Heinemann, Luca; Möllers, Klara Maria; Ahmed, Helal Mohammed Mohammed; Wei, Lanying; Sun, Kaiyan; Nimmagadda, Subbaiah Chary; Frank, Daria; Baumann, Anja; Poos, Alexandra M.; Dugas, Martin; Varghese, Julian; Raab, Marc-Steffen; et al. (Frontiers in Oncology, 2022)
The microenvironment of cancer cells is receiving increasing attention as an important factor influencing the progression and prognosis of tumor diseases. In Multiple Myeloma (MM), a hematological cancer of plasma cells, mesenchymal stem cells (MSC) represent an integral part of the bone marrow niche and tumor microenvironment. It has been described that MM-cells alter MSCs in a way, that MM-associated MSCs promote the proliferation and survival of MM-cells. Yet our understanding of molecular mechanisms governing the interaction between MM-cells and MSCs and whether this can be targeted for therapeutic interventions is limited. To identify potential molecular targets, we examined MSCs by RNA-sequencing and Western Blot analysis. We report that MSCs from MM-patients with active disease (MM-Act-MSC) show a distinct gene expression profile as compared to MSCs from patients with other (non-) malignant diseases (CTR-MSC). Of note, we detected a significant enrichment of the PI3K-AKT-mTOR Hallmark gene set in MM-Act-MSCs and further confirmed increased levels of related proteins in these MSCs. Pictilisib, a pan-PI3K-inhibitor, selectively reduced the proliferation of MM-Act-MSCs as compared to CTR-MSCs. Further, pictilisib treatment impaired the MM-promoting function of MM-Act-MSCs. Our data thus provide a deeper insight into the molecular signature and function of MSCs associated with MM and show that targeting PI3K-AKT-mTOR signaling in MSCs may represent an additional therapeutic pathway in the treatment of MM-patients.